Virtual reality as a chemotherapy support in treatment of anxiety and fatigue in patients with cancer: A systematic review and meta-analysis and future research directions - Sebastian Rutkowski; Oliver Czech; Adam Wrzeciono; Paweł Kiper; Joanna Szczepańska-Gieracha; Iwona Malicka (Elsevier, 2021)
Objective: The aim of this systematic review was to analyse the effectiveness of virtual reality intervention as an aid for treatment-related anxiety and fatigue in cancer patients undergoing chemotherapy. The term chemotherapy was assumed without distinction regarding type. Methods: The inclusion criteria were (1) randomised controlled trials or crossover studies, (2) adult cancer patients undergoing chemotherapy, (3) treatment with VR scenarios providing distraction during chemotherapy, and (4) with pain, anxiety, fatigue, fear, or symptom distress as the measured outcomes. Articles in English, Polish, and Italian were sought. For the methodological quality assessment of risk of bias, likewise statistical analysis and meta-analysis the RevMan version 5.4 software and the Cochrane Risk of Bias Tool were used. Two authors independently analysed the following databases for relevant research articles: PubMed, Scopus, Cochrane Library, Web of Science, and Embase. Results: From a total of 2543 records, 6 studies met the inclusion criteria for qualitative analysis. At the end of the process, 3 studies remained for quantitative analysis. The systematic review includes three randomised, controlled studies and three crossover studies with an overall sample size of 453 patients. The analysis of the primary outcomes chosen for each study revealed no significant differences between the control and experimental conditions. Moreover, an important factor influencing the results of the review and meta-analysis was the poor quality of the publications available on the topic of distraction during chemotherapy. Conclusion: Due to the low research standards, the results do not provide an unambiguous answer to the research question. The most important limitations result from the small number of trials, the generally small sample sizes, and the differences in study design.